Recent Advances in Dry Reforming of Methane Over Ni-Based Catalysts - Bawadi, Abdullah; Nur Azeanni, Abd Ghani; Vo, Dai-Viet N. (Elsevier Ltd., 2017)
A steady increase in atmospheric carbon dioxide (CO2) and methane concentrations in recent decades has sparked interest among researchers around the globe to find quick solutions to this problem. One viable option is a utilization of CO2 with methane to produce syngas via catalytic reforming. In this paper, a comprehensive review has been conducted on the role and performance of Ni-based catalysts in the CO2 reforming of methane (sometimes called dry reforming of methane, DRM). Coke-resistance is the key ingredient in good catalyst formulation; it is, therefore, paramount in a choice of catalyst supports, promoters, and reaction conditions. Catalyst supports that have a strong metal-support interaction created during the catalyst preparation exhibit highest stability, high thermal resistance and high coke resistance. In addition, the outlook of the Ni-based catalysts has been proposed to provide researchers with critical information related to the future direction of Ni-based catalysts in industrial settings. Among others, it has been a great interest among researchers to synthesize catalyst supports from cellulosic materials (plant-based materials). The unique properties of the cellulose which are a welldefined structure and superior mechanical strength could enhance the catalytic activity in the DRM reaction.